Зависните имперфектни да-конструкции и нивните англиски корелати - Gj. Atanasovska, Katarina; Cvеtkoski, Vladimir (Slavia Centralis, 2020)
The paper describes subordinated imperfective da-constructions (SI da-constructions) in Macedonian by examining their meanings, use and English equivalents. Their use, their semantic and functional properties and their English equivalents have also been described. Any possible similarities or differences between the two languages have been indicated in terms of meaning and use of the formal counterparts. The paper’s starting hypothesis is that, apart from appearing in the protasis of unreal, counterfactive conditionals, SI da-constructions can be found in other contexts with different meanings.
Keywords: subordinated imperfective da-constructions; Macedonian; English; subjunctive; contrastive analysis